2014
DOI: 10.1007/s00299-013-1556-5
|View full text |Cite
|
Sign up to set email alerts
|

Co-suppression of synthesis of major α-kafirin sub-class together with γ-kafirin-1 and γ-kafirin-2 required for substantially improved protein digestibility in transgenic sorghum

Abstract: The combined suppression of only two genes, γ kafirin-1 (25 kDa) and γ-kafirin-2 (50 kDa), significantly increases sorghum kafirin in vitro digestibility. Co-suppression of a third gene, α-kafirin A1 (25 kDa), in addition to the two genes increases the digestibility further. The high-digestibility trait has previously only been obtained either through the co-suppression of six kafirin genes (α-A1, 25 kDa; α-B1, 19 kDa; α-B2, 22 kDa; γ-kaf1, 27 kDa; γ-kaf 2, 50 kDa; and δ-kaf 2, 18 kDa) or through random chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 51 publications
3
48
0
Order By: Relevance
“…However, their actual dough properties and leavened bread-making quality were not investigated. Kumar et al (2012), in general agreement with the findings of Da Silva et al (2011a) and Grootboom et al (2014), showed that γ-kafirin suppression alone did not alone alter protein body structure, but attributed this to the silencing of a predicted 29 kDa α-kafirin sub-class (presumably a cysteine-poor protein). With the aim of improving the roti (flatbread) making quality of sorghum, gene cassettes containing a wheat HMW-GS gene driven by the γ-kafirin promoter have been constructed (Mishra et al, 2008).…”
Section: Genetic Modification Of Storage Protein Expressionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, their actual dough properties and leavened bread-making quality were not investigated. Kumar et al (2012), in general agreement with the findings of Da Silva et al (2011a) and Grootboom et al (2014), showed that γ-kafirin suppression alone did not alone alter protein body structure, but attributed this to the silencing of a predicted 29 kDa α-kafirin sub-class (presumably a cysteine-poor protein). With the aim of improving the roti (flatbread) making quality of sorghum, gene cassettes containing a wheat HMW-GS gene driven by the γ-kafirin promoter have been constructed (Mishra et al, 2008).…”
Section: Genetic Modification Of Storage Protein Expressionsupporting
confidence: 81%
“…Da Silva et al (2011a) and Grootboom et al (2014) showed that co-suppression of the synthesis of α-, γ-, β-and δ-kafirins modified the structure of the protein bodies so that they had invaginations like those of the high protein digestibility mutant (Oria et al, 2000) and that they were less densely packed in the endosperm. These changes resulted in the endosperm structure becoming floury.…”
Section: Genetic Modification Of Storage Protein Expressionmentioning
confidence: 99%
“…Previous analyses found complete suppression of the targeted kafirin proteins and a significant improvement (of up to 37%) in the in vitro protein digestibility of the transgenic grains (Grootboom et al, 2014). The transgenic lines represent the fifth generation of self-crossing progenies from T 0 sorghum transformants, which were originally produced using particle bombardment as described in Grootboom et al (2014).…”
Section: Methodsmentioning
confidence: 95%
“…Previous analyses found complete suppression of the targeted kafirin proteins and a significant improvement (of up to 37%) in the in vitro protein digestibility of the transgenic grains (Grootboom et al, 2014). The transgenic lines represent the fifth generation of self-crossing progenies from T 0 sorghum transformants, which were originally produced using particle bombardment as described in Grootboom et al (2014). Plants from each independent transgenic line (hereafter referred to as 42-1 and 42-2) and the parental control cultivar P898012 (hereafter referred to as WT), were grown in pots in a containment glasshouse located at the Centre for Scientific and Industrial Research (CSIR) Biosciences Division (Pretoria, South Africa).…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation